Director's report on the activity and management of the International Bureau of Weights and Measures, 1 January 2014 - 31 December 2014 - (Bureau International des Poids et Mesures (BIPM) SevresFR, 2015)
Presents the annual report of the BIPM.
Keywords: WEIGHTS AND MEASURES